The Occurrence, Causes, and Prognosis of Dysphonia and Repeated Injury to the Laryngeal Nerve after Anterior Cervical Spine Surgery - Badal Khan, Shafaat Hussain, Luqman Asghar, Nasrul Huda, Tauseef Raza, Ahmed Waqas, Mian Iftikhar Ul Haq, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: There is a chance of dysphonia and recurrent laryngeal nerve (RLN) injury with anterior cervical spine surgery (ACSS), although it is a successful treatment for many cervical spine problems. Objective: Aim was to determine the incidence, risk factors, and outcomes of recurrent laryngeal nerve injury and dysphonia following anterior cervical spine surgery. Methods: Total 164 patients of recurrent laryngeal nerve injury and dysphonia were presented in this study, after getting informed written consent detailed demographics were recorded. All the patients were undergoing for anterior cervical spine surgery. Outcomes were recorded. SPSS 22.0 was used to analyze all data. Results: There were 96 (58.5%) males and 68 (41.5%) females among all cases. Patients mean age was 48.13 years. Majority of the cases were married. 75 (44.6%) cases were educated. Frequency of RLN was found in 102 (60.7%) cases and dysphonia in 66 (39.3%) cases. Most common risk factor for dysphonia was throat infections and smoking and for RLN was anatomical variations in the nerve's path, thyroid cancer, large goiters and previous neck surgery. Mean duration of surgery in RLN was 112.4 min and in dysphonia was 76.8 minutes. Frequency of complication in RLN was 31 (30.4%) and in dysphonia was 17 (25.8%). Conclusion: We concluded in this study patients with RLN and dysphonia had high frequency of complications. Most common risk factors were anatomical variations in the nerve's path for RLN and throat infection for dysphonia. Keywords: RLN, Dysphonia, Anterior cervical spine surgery, Risk factors